The Application of Geculan Bocah Dance in Improving Children’s Social Emotional Development Aged 5-6 Years in Pertiwi Kindergarten, Pakis Sub District, Magelang Regency - Rumiyati, Rumiyati; Khamidun, Khamidun (Jurusan PGPAUD FIP UNNES, 2017)
Children’s social emotional development aged 5-6 year in Permendikbud number 137 year2014 on national education early childhood standards there are level of achievement in child development (STPPA) PAUD 2013 curriculum which consists of self-awareness, a sense of responsibility for themselves and other people, and social behavior. Self-awareness covering on how to show the ability of themselves based on situation, shows prudence to the unknown people (then brought belief in a right adults), and knowing his own feelings and work them in (to exercise restraint in appropriately). A sense of responsibility of themselves and others covering on how she knows her right, obey the class rules (rules, activities), organize themselves, and responsible for her own doing for her own goodness. The act of pro-social is by playing with their peer, knowing others feeling and response it appropriately, sharing with others, appreciate others’ right/argument/and works, using acceptable norm in solving the problem (using their logical thinking in solving their problems), being cooperative with their friends, being tolerant, expressing their true feeling (happy, sad, enthusiastic etc), and acknowledge themselves with norms in their surroundings. The Purpose of this study is to find an improvement in children’s social emotional development aged 5-6 years in kindergarten in Pertiwi kindergarten Pakis sub district Magelang regency through Geculan Bocah Dance treatment. A method of this research is experimental research with one group pretest posttest design. In this case treatment is given to children aged 5-6 years which consist of 33 children. Technique of analyzing data is using paired sample t-test. Children’s social emotional development aged 5-6 years in Pertiwi kindergarten Pakis sub district at first of 47,24 %. Then Geculan Bocah dance treatment was given. Children’s social emotional development aged 5-6 years in Pertiwi kindergarten Pakis sub district increased to 82,12 %.The size of the increase occurring of 34,88%. Conclusion that obtained in this research is: there has been increasing on children’s social emotional development aged 5-6 years in Pertiwi kindergarten Pakis sub district Magelang regency.